Anecdote Text Vs Spoof Text - Feriyanti Elina Gultom (BAHAS, 2016)
It is often find understanding about the funny story in our society life. Every funny story is often defined as anecdote. In this term, anecdote is pointing to “cerita lelucon” or “konyol”. Most the story are funny because they have unpredictable funny things in the end. All those types of story are often socially called anecdote and they are going on. However, the unpredictable thing in the end of story which is often funny is called twist. This Twist, in term of text type, belongs to spoof. While in the generic structure of anecdote, we can not find the twist. So it might be the funny story which we often hear in our social life and defined as anecdote story is not the the anecdote text in term of text types we are learning. Commonly it is defined spoof and anecdote are similar, even both are same. Spoof and anecdote tend to be defined as text which relate to funny story and unusual incidents. It can be true as both bring the function mostly to entertain and share to readers. But, actually both are different. Key Words: Text, Anecdote and spoof